Benefits of an Abscission Agent in Mechanical Harvesting of Citrus - Fritz Roka; Jackie Burns; Jim Syvertsen; Robert Ebel (EDIS, 2008)
FE752, a 4-page fact sheet by Fritz Roka, Jackie Burns, Jim Syvertsen, and Robert Ebel, describes research into the use of abscission agents in mechanical harvesting, to extend the harvesting window to later in the season, permit faster harvesting speed, enhance fruit recovery percentages, and reduce tree damage. Includes references. Published by the UF Department of Food and Resource Economics, September 2008.